Rate of pachymeningeal failure following adjuvant WBRT vs SRS in patients with brain metastases - Enrique Gutierrez-Valencia; Aristotelis Kalyvas; Kurl Jamora; Kaiyun Yang; Ruth Lau; Benazir Khan; Barbara-Ann Millar; Normand Laperriere; Tatiana Conrad; Alejandro Berlin; Jessica Weiss; Xuan Li; et al. (Clinical and Translational Radiation Oncology, 2024)
Background: Stereotactic radiosurgery (SRS) has supplanted whole brain radiotherapy (WBRT) as standard-of-care adjuvant treatment following surgery for brain metastasis (BrM). Concomitant with the adoption of adjuvant SRS, a new pattern of failure termed “Pachymeningeal failure” (PMF) has emerged. Methods: We reviewed a prospective registry of 264 BrM patients; 145 and 119 were treated adjuvantly with WBRT and SRS, respectively. The Cox proportional hazards model was used to identify variables correlating to outcomes. Outcomes were calculated using the cumulative incidence (CI) method. Univariate (UVA) and multivariate analyses (MVA) were done to identify factors associated with PMF. Results: CI of PMF was 2 % and 18 % at 12 months, and 2 % and 23 % at 24 months for WRBT and SRS, respectively (p < 0.001). The CI of classic leptomeningeal disease (LMD) was 3 % and 4 % at 12 months, and 6 % and 6 % at 24 months for WBRT and SRS, respectively (P = 0.67). On UVA, adjuvant SRS [HR 9.75 (3.43–27.68) (P < 0.001)]; preoperative dural contact (PDC) [HR 6.78 (1.64–28.10) (P = 0.008)]; GPA score [HR 1.64 (1.11–2.42) (P = 0.012)]; and lung EGFR/ALK status [HR 3.11 (1.02–9.45) (P = 0.045)]; were associated with PMF risk. On MVA, adjuvant SRS [HR 8.15 (2.69–24.7) (P < 0.001)]; and PDC [HR 6.28 (1.51–26.1) (P = 0.012)] remained associated with PMF. Conclusions: Preoperative dural contact and adjuvant SRS instead of adjuvant WBRT were associated with an increased risk of PMF. Strategies to improve pachymeningeal radiation coverage to sterilize at risk pachymeninges should be investigated.